2020
DOI: 10.1021/acs.langmuir.0c02339
|View full text |Cite
|
Sign up to set email alerts
|

Porous Ceramics via Processable Pickering Emulsion Stabilized by Oppositely Charged Colloids

Abstract: We report a method to produce processable Pickering emulsions in which electrostatic heteroaggregation of oppositely charged fumed silica and alumina particles is exploited. The ability of weakly charged heteroaggregates to adsorb to the oil–water interface favors the formation of highly stable emulsions. A control over the microstructure and rheology of the Pickering emulsion is demonstrated by tuning parameters such as composition, pH, and total concentration of particles. The Pickering emulsions formed unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Controlled drying of the oil-in-water emulsion gels, which upon evaporation of both water and oil results in a ceramic green body, constitutes an important step in the fabrication of porous ceramic. , The conditions used for drying must be such that the pore former, i.e., which in this case predominantly is oil, evaporates without any damage to the shape and structural integrity of the final ceramic green body. The gelled emulsions were dried under a controlled environment in a humidity chamber maintained at 35 °C and 55% RH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Controlled drying of the oil-in-water emulsion gels, which upon evaporation of both water and oil results in a ceramic green body, constitutes an important step in the fabrication of porous ceramic. , The conditions used for drying must be such that the pore former, i.e., which in this case predominantly is oil, evaporates without any damage to the shape and structural integrity of the final ceramic green body. The gelled emulsions were dried under a controlled environment in a humidity chamber maintained at 35 °C and 55% RH.…”
Section: Resultsmentioning
confidence: 99%
“…The emulsion stabilized by heteroaggregates of oppositely charged particle−polyelectrolyte mixture was dried in a humidity chamber under controlled conditions (at 35 °C and 55% RH) to obtain a green emulsion body. 32 Thermogravimetric analysis (TGA) was performed for the ceramic green body using a thermogravimetric analyzer (TA Instruments). The sample was subjected to a temperature ramp at 10 °C/min under air atmosphere.…”
Section: N D D Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, using two types of particles has been shown to synergistically stabilize Pickering emulsions, especially when the use of either type of particle alone does not stabilize the emulsion. , Different stabilization mechanisms have been proposed to account for the emulsion stabilized by dual particles. Binks et al, for example, described how hetero-aggregations formed through the electrostatic attraction of silica particles with opposite charges before emulsification has suitable wettability for stabilizing the Pickering emulsion . Similarly, Nallamilli et al found that hetero-aggregations of oppositely charged polystyrene (PS) particles assemble easily at the o/w interface and further rearrange for forming a monolayer of closely packed particles at the interface .…”
Section: Introductionmentioning
confidence: 99%